Adaptation et validation française de l’échelle Job Demands-Resources (JD-R) en contexte scolaire - Oger, Marie; Broc, Guillaume; Rotonda, Christine; Tarquinio, Cyril; Martin-Krumm, Charles (Canadian Journal of Education/Revue canadienne de l'éducation, 2022)
The aim of this article is to analyze, as has been done with adults in their professional field, how young people in school perceive their work environment. The main objective is to study the operationalization of the theoretical model “Job Demands-Resources (JD-R)” of Demerouti and al. (2001) in the school context. The secondary objective is to validate a scale adapted to the school context that makes it possible to determine the level of both demands and resources as perceived by the students within the school. In a first study, a scale was adapted, then administered, to 414 middle and high school students. The results of exploratory and then confirmatory factor analyses indicated a two-dimensional structure (demands/resources) with three items each (physical, motivational and cognitive) in accordance with the original version. The psychometric properties of the scale were found to be satisfactory. Using causal path analyses, the second study with 56 students highlighted the relationship between the JD-R model transposed to schools and school burnout. The results collected at three points in time reveal that the demands and resources at T1 predict those at T2, as was assumed. However, only resources at T2 predict burnout at T3. In the end, the process analysis reveals the effects of students' perceived level of resources at T1 on school burnout at T3, but indicates no significant effect of demands. In conclusion, the model was partially validated showing relationships between changes in demands, resources and their effects on burnout.